Detonation of a nitromethane-based energetic mixture driven by electrical wire explosion. (28th October 2021) - Shi, Huantong; Hu, Yujia; Li, Tuan; Tao, Zhanping; Li, Xingwen; Wu, Jian; Murphy, Anthony B; Qiu, Aici
Abstract: The combination of energetic material (EM) and an electrical wire explosion (EWE) is an important way to achieve effective release and conversion of electrical and chemical energy, e.g. by generating strong underwater shock waves (SWs) that can be used for dynamic reservoir fracturing in unconventional gas exploitation. This letter proposes a mud-like EM composed of nitromethane, aluminium and copper oxide powder, which can be detonated directly by a tungsten wire explosion. The detonation and successive deflagration result in notably enhanced SWs: with 2.8 g EM, the SW amplitude, impulse and energy are respectively increased by 1.7, 2.1, and 7.9 times compared to an optimal underwater EWE. A direct thermal initiation mechanism for the detonation process is proposed, with the exploding wire, the Joule heating along the current path in the EM and the Al/CuO thermite reaction all serving as heat sources. It is found that the Joule heating and chemical reactions reinforce each other, which is likely the key to the 'easy' detonation of nitromethane.